1999
DOI: 10.1002/(sici)1097-4555(199907)30:7<605::aid-jrs427>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-sensitive resonance CARS spectroscopy of magnesium octaethylporphine

Abstract: Polarization-sensitive resonance coherent anti-Stokes Raman scattering spectroscopy of magnesium octaethylporphine (MgOEP) in dichloromethane is reported. The measurements were performed in resonance with the Q-band electronic absorption where linear resonance Raman spectroscopic measurements were foiled by excessive fluorescence. A high porphyrin concentration allowed direct identification of the different vibrational mode symmetries. Complementary vibrational information was obtained from B -band resonance R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Because of the considerably higher sensitivity of vibrational spectroscopy versus electronic absorption spectroscopy for determining the molecular symmetry, it can be concluded that MgOEP is not of ideal D 4h symmetry. These results are in line with the findings of a comparable resonance coherent anti-Stokes Raman scattering (CARS) study on MgOEP [34] and the quantum mechanical calculations presented below.…”
Section: Mgoepsupporting
confidence: 90%
“…Because of the considerably higher sensitivity of vibrational spectroscopy versus electronic absorption spectroscopy for determining the molecular symmetry, it can be concluded that MgOEP is not of ideal D 4h symmetry. These results are in line with the findings of a comparable resonance coherent anti-Stokes Raman scattering (CARS) study on MgOEP [34] and the quantum mechanical calculations presented below.…”
Section: Mgoepsupporting
confidence: 90%
“…Such a pattern of mode-selective resonance enhancement is consistent with that typically reported for metallo-octaethylporphyrins, which are excited in the Q 00 -Q 01 absorption range. 5,7,9,18,19,21,23 The most pronounced enhancement is undergone by the antisymmetric A 2g modes ( 19 , 21 and 22 ), which are seen to dominate all spectra except spectrum (d) in Fig. 3.…”
Section: Vibrational Assignment In Zn-oepmentioning
confidence: 95%
“…Recalling that the position of the peak along the CARS wavenumber axis is given approximately by the arithmetic mean wavenumber of two vibrational modes beating with each other and that the peak location along the FFT wavenumber axis corresponds to the wavenumber difference of the two modes, we can compare the peak position to the vibrational mode spectrum of MgOEP reported in the literature. 28 We thus attribute this peak to a quantum beating between the two modes 10 and 11 . Both of these modes possess b 1g symmetry and they are located at wavenumber positions of 1606 and 1552 cm 1 , respectively.…”
Section: Spectrally Dispersed Transient Cars Signalmentioning
confidence: 90%
“…The assignment of these peaks to vibrational modes was performed by a comparison of our results with data obtained from resonance Raman measurements and ns-CARS experiments. 28,30 To this end we took advantage of the fact that the FFT wavenumber position of the peaks in the PSD plots directly corresponds to the wavenumber difference Q j Q k of modes j and k . This information allowed us to derive spectral information on the relative peak positions of individual vibrational modes from our measurements.…”
Section: Spectrally Dispersed Cars Signals Of Mgoep For Different Excmentioning
confidence: 99%